Perspectives of physicians regarding screening patients at risk of hepatocellular carcinoma - Bharadwaj, Shishira (Gastroenterol Rep (Oxf), 2016)
Background and aims: Screening patients at risk for hepatocellular carcinoma (HCC) facilitates early detection of disease, with improved outcome. The most common causes of HCC include chronic viral hepatitis infection—namely hepatitis B, hepatitis C, and cirrhosis. The aim of this study was to assess the awareness of screening among physicians involved in the management of patients at risk for HCC. Methods: Three hundred physicians from three academic centers were invited to participate in a mailed survey questionnaire. The main outcome measure was physicians' knowledge of the current HCC screening guidelines. Demographic and clinical variables were obtained from the survey questionnaire. Results: A total of 177 (59.0%) out of the 300 invited physicians responded to the survey questionnaire, including faculty members (n = 129), residents (n = 46), and fellows (n = 2). The specialty areas of the responding physicians were internal medicine (62.1%), family medicine (16.4%), gastroenterology (15.3%), oncology (3.4%) and others (2.8%). The number of physicians who performed HCC screening in patients with cirrhosis secondary to chronic hepatitis B and chronic hepatitis C infection were 163 (92.1%) and 167 (94.4%), respectively; 35.0% of them used alpha-fetoprotein (AFP) every 6 months, while 22.0% used imaging modalities every 6 months to screen for HCC. Further, 22 physicians (12.4%) did not check for serum AFP levels and 33 (18.6%) never used imaging to screen for HCC. Conclusion: The majority of the participating physicians screen high-risk patients for HCC. However, the most appropriate modality of screening (i.e. imaging) is not employed by most physicians and there is greater reliance on AFP levels.